Single Near‐Infrared Emissive Polymer Nanoparticles as Versatile Phototheranostics - Liang Guo; Guangle Niu; Xiuli Zheng; Jiechao Ge; Weimin Liu; Qingyan Jia; Panpan Zhang; Hongyan Zhang; Pengfei Wang (Advanced Science, 2017)
Abstract Attaining consistently high performance of diagnostic and therapeutic functions in one single nanoplatform is of great significance for nanomedicine. This study demonstrates the use of donor–acceptor (D–A) structured polymer (TBT) to develop a smart “all‐five‐in‐one” theranostic that conveniently integrates fluorescence/photoacoustic/thermal imaging and photodynamic/photothermal therapy into single nanoparticle. The prepared nanoparticles (TBTPNPs) exhibit near‐infrared emission, high water solubility, excellent light resistance, good pH stability, and negligible toxicity. Additionally, the TBTPNPs exhibit an excellent singlet oxygen (1O2) quantum yield (40%) and high photothermal conversion efficiency (37.1%) under single‐laser irradiation (635 nm). Apart from their two phototherapeutic modalities, fluorescence, photoacoustic signals, and thermal imaging in vivo can be simultaneously achieved because of their enhanced permeability and retention effects. This work demonstrates that the prepared TBTPNPs are “all‐five‐in‐one” phototheranostic agents that can exhibit properties to satisfy the “one‐fits‐all” requirement for future phototheranostic applications. Thus, the prepared TBTPNPs can provide fundamental insights into the development of PNP‐based nanoagents for cancer therapy.